Large scale microwave synthesis of Metal-Organic Frameworks - Thomas-Hillman, Ieuan (2021)
This thesis contains a collection of manuscripts and commentary reporting on the microwave synthesis of metal-organic frameworks (MOFs), a broad class of porous materials. The central aim of this scheme of work was to use microwave heating solutions to realise the rapid synthesis of MOF materials. This has the potential to enable large scale production of these materials whilst also elucidating on the consequences of using this alternative heating method and the underlying mechanism by which the materials are synthesised.